DEVELOPMENT OF JAMU KUNYIT PRODUCTS USING VALUE ENGINEERING METHOD (Case Study: Madura Sari Sampang) - Rakhmawati; Akhmad Dwi Kurniawan; Darimiyya Hidayati (International Journal of Innovations in Engineering Research and Technology, 2022)
Turmeric herb is a typical Indonesian herbal drink which is usually made from turmeric rhizome. Compounds contained in turmeric (curcumin and essential oils) have important roles as antioxidants, antitumors, anti-cancer, antisenile, lowering fat and cholesterol levels in the blood and liver, antimicrobial, antiseptic and anti-inflammatory (Mattiro et al. 2020). Value engineering is one method that can be used in the development of this product. According to (Ulya et al. 2020) the purpose of this study is to find out the attributes and the best alternatives in the development of herbal turmeric products using the value engineering method according to consumer desires. This research will be useful to focus or direct the policies that have been carried out in the value engineering development strategy based on the structure that has been built for product development of herbal turmeric. The results obtained for the 3 selected attributes are materials, ingredients and packaging. The selected dip turmeric herbal product is the 1st alternative with a value of 1.106. The alternative is turmeric + palm sugar, a 2:1 ratio with box packaging. The ratio of added value of herbal dip using the value engineering method is 87.570% with a profit percentage of 46.687% from the previous product and an added value of Rp. 7,003